Hermeneutika wa At-ta’wil: Al-Muqaranatu fi Minhaji Tafsir Al-Ma’ani - Adli Haaj Yacoob; Hafidz Fadli Achmad (Studia Quranika, 2020)
This study discusses hermeneutics in terms of its history and its use as a method of analysis as well as its comparison with the ta’wîl method in the interpretation of texts. This study used a qualilative method with a literature review approach and comparative analysis. Hermeneutics was originally a study of text interpretation in the Bible whereas ta’wîl was a study of interpretations of the Quran particularly for verses that have inner meanings. Until their scientific development, there are resemblances Both of two studies, but there are also differences in the fundamental principles between them.Thi study almed to show the comparison between two studies it appears that there are several comparisons in the usage history, in the requirement in explaning the verses. Then the technique in using those methods.